A Visual Prompt-Based Mobile Learning System for Improved Algebraic Understanding in Students With Learning Disabilities - Peng-Chan Chang; Rong-Ho Lin (IEEE Access)
This study aims to address the significant learning challenges faced by students with learning disabilities, particularly in mastering algebraic concepts. Traditional rule-based instruction often exacerbates these challenges, highlighting the need for more effective teaching methodologies. While existing literature confirms the effectiveness of both prompt-based learning and computer-assisted instruction in math education, very few studies have looked at combining mobile technology with prompt-based learning approaches for algebra instruction. In response to this gap, we propose a Visual Prompt-Based Mobile Learning Strategy (VPML). This innovative method is specifically designed to enhance the understanding of basic algebra, focusing on linear equations. Utilizing a quasi-experimental design, we conducted a comprehensive 12-week study to assess the impact of VPML on learning outcomes among students with learning disabilities. The results indicate significant improvements in the students’ abilities to comprehend and solve linear equations when taught via the VPML strategy. Therefore, this study serves not only as a validation of the VPML approach but also as a meaningful contribution to the ongoing discourse on optimizing educational interventions for students with learning disabilities in algebra.